Improving The Internalization Of Religious Values Through Strengthening The Tpa “Raudhotul Athfal” In Trihanggo Village, Gamping, Sleman, The Special Region Of Yogyakarta - Aji, Juhari sasmito; Pahlevi, Reza Widhar; Hayati, Kemala (LPPM Universitas Timor, 2024)
TPA is a Quran Education Park that accommodates early childhood in carrying out complex religious learning, such as Islamic history, daily prayer, reading and writing the Qur'an, tajweed, mahfudzot, etc. The implementation of informal learning is motivated by moral distortions that spread among Generation-Z, this is marked by early marriage due to pregnancy outside marriage. Therefore, the implementation of this service is important because it supports the strengthening of moral renewal which is the foundation and affects the character of children. Like TPA Raudhatul Athfal Dusun Biru which provides learning the values of the Qur'an. With the number of students 37-40 children. However, in teaching and managing the landfill, Raudhatul Athfal experienced problems, including lack of consistency and commitment of landfill managers, lack of competence and human resource skills in managing, inactivity of landfill participants, and poor recording of financial statements. From these problems, the service team provides solutive actions with socialization, training and mentoring methods according to the problems faced, and provides target measures to determine the success of service.